Prepulse Inhibition in HIV-Associated Neurocognitive Disorders - Minassian, Arpi; Henry, Brook L.; Woods, Steven Paul; Vaida, Florin; Grant, Igor; Geyer, Mark A.; Perry, William (Journal of the International Neuropsychological Society, 2013)
Sensorimotor inhibition, or the ability to filter out excessive or irrelevant information, theoretically supports a variety of higher-level cognitive functions. Impaired inhibition may be associated with increased impulsive and risky behavior in everyday life. Individuals infected with HIV frequently show impairment on tests of neurocognitive function, but sensorimotor inhibition in this population has not been studied and may be a contributor to the profile of HIV-associated neurocognitive disorders (HAND). Thirty-seven HIV-infected individuals (15 with HAND) and 48 non-infected comparison subjects were assessed for prepulse inhibition (PPI), an eyeblink startle paradigm measuring sensorimotor gating. Although HIV status alone was not associated with PPI deficits, HIV-positive participants meeting criteria for HAND showed impaired PPI compared to cognitively intact HIV-positive subjects. In HIV-positive subjects, PPI was correlated with working memory but was not associated with antiretroviral therapy or illness factors. In conclusion, sensorimotor disinhibition in HIV accompanies deficits in higher-order cognitive functions, although the causal direction of this relationship requires investigation. Subsequent research on the role of sensorimotor gating on decision-making and risk behaviors in HIV may be indicated. (JINS, 2013, 19, 1–9)